We were soldiers - Wallace, Randall; Glennie-Smith, Nick; Gibson, Mel; Stowe, Madeleine; Kinnear, Greg 1963-; Elliott, Sam 1944-; Klein, Chris 1979-; Russell, Keri 1976-; Pepper, Barry 1970-; Moore, Harold G.; Galloway, Joseph L.
Lt. Col. Hal Moore is the commander of the First Battalion, Seventh Cavalry. As part of the Pleiku Campaign of late 1965, Moore is assigned to action at Landing Zone X-Ray in the Ia Drang Valley, an area known to be overrun by North Vietnamese troops and nicknamed "The Valley of Death." Moore soon finds himself and his men contained to an area about the size of a football field, surrounded by more than 2,000 enemy troops and engaged in the first major battle of the war. Heroism becomes the order of the day as the men refuse to yield, in spite of heavy losses of life.